New high collapse model to calculate collapse strength for casing. (December 2015) - Deng, Kuanhai; Lin, Yuanhua; Qiang, Hu; Zeng, Dezhi; Sun, Yongxing; Xinxin, Lin
Abstract: With the increase of the ultra-deep well for oil and gas exploration and development, the conventional America Petroleum Institute (API) casing strength cannot meet the strength criteria of deep and ultra-deep wells. However, the high collapse casing (HCC) shows a higher resistance to collapse pressure so that it has obviously improved collapse properties in excess of API ratings. For limitation of the API model, the ISO collapse strength model with manufacturing imperfections has been proposed, which improves the casing strength calculation accuracy and increases the benefits for casing strength design, rather than just using API model. But the study on the ISO collapse model shows that it is inappropriate to predict the collapse strength of HCC of all sizes. Hence, a new high collapse model with manufacturing imperfections, strength differential (SD) effect, yield-to-tensile strength ratio, material hardening and intermediate principal stress effect, which can predict the collapse strength of HCC, has been presented based on unified strength theory. Numerical and experimental comparisons show that the calculation results of new high collapse model are much closer to the test data than that of API and ISO models, which will make great improvements in the casing design of deep and ultra-deep wells on the basis of HCC material safety. Highlights: One new high collapse model computing collapse strength of casing has been presented. Manufacturing imperfections and SD effect have been taken into account in the model. Numerical and experimental comparisons validate calculation accuracy of the model.